Circulating Th1, Th2, Th17, Treg, and PD-1 Levels in Patients with Brucellosis - Rongjiong Zheng; Songsong Xie; Qiong Zhang; Ling Cao; Shaniya Niyazi; Xiaobo Lu; Lihua Sun; Yan Zhou; Yuexin Zhang; Kai Wang (Journal of Immunology Research)
Brucella is an intracellular infection bacterium; the pathogenesis of Brucella and chronicity of infection may be related to the immune response of T cells. T lymphocytes mainly participate in cellular immune response. The extent of different T cell subsets imbalanced and their function dysregulated in patients with brucellosis remain not explicit. We grouped patients at different stages (acute, chronic, and convalescent). The frequencies of Th1, Th2, Th17, Treg, and PD-1 (programmed cell death protein 1) in peripheral blood were examined by flow cytometry, and the expressions of T lymphocyte cytokines in serum were detected by cytometric bead array. Th1, Th17, and Treg cell immunity was predominant in the acute stage, while Th2, Th17, and Treg cell immunity was predominant in the chronic stage. The expressions of PD-1 on CD4+ and CD8+ T lymphocytes were significantly different in acute and chronic patients. The percentages of Th1 cells in convalescent patients were still higher than those in healthy controls within one year after withdrawal. The expression of T lymphocyte cytokines in serum was different in patients at different stages. These results indicate that peripheral T lymphocyte immunity was involved in patients with brucellosis and represents a target for the preclinical and clinical assessment of novel immunomodulating therapeutics. The patients’ immune function had not completely recovered in a short period of time during convalescence, so long-term follow-up of convalescent patients is needed.